2012
DOI: 10.5053/ekoloji.2011.821
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Accumulation in Some Vegetables and Soils in Istanbul

Abstract: This work was designed to assess the concentration of six toxic metals in the soil and in unwashed and washed samples of different vegetable species (Petroselinum crispum, Brassica oleraceae var. acephala, Beta vulgaris var. cicla collected from six different sites (stream side, inner city, industrial, suburban, roadside, and rural) in Istanbul in 2007. Concentrations of Cd, Cr, Cu, Ni, Pb, and Zn were determined by using ICP-OES. It was found that the average highest values of metal accumulations were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 28 publications
3
35
1
4
Order By: Relevance
“…In fact, high soil pH, clay and organic matter content are not supporting Pb uptake via roots. On the other hand, Kylander et al (2003) analyzed in Accra a Pb distribution following traffic density as also shown in other studies (Baye and Hymete 2010;Osma et al 2013;Teju et al 2012). Since lead is not biodegradable, and highly immobile, once soil has become contaminated, it remains a long-term source of dust exposure, although lead-free gasoline dominates today's market.…”
Section: Heavy Metals In Vegetablesmentioning
confidence: 54%
“…In fact, high soil pH, clay and organic matter content are not supporting Pb uptake via roots. On the other hand, Kylander et al (2003) analyzed in Accra a Pb distribution following traffic density as also shown in other studies (Baye and Hymete 2010;Osma et al 2013;Teju et al 2012). Since lead is not biodegradable, and highly immobile, once soil has become contaminated, it remains a long-term source of dust exposure, although lead-free gasoline dominates today's market.…”
Section: Heavy Metals In Vegetablesmentioning
confidence: 54%
“…The samples were divided into two sub-samples; the samples in the first sub-group were thoroughly washed several times with tap water, and subsequently by distilled water in order to to remove dust particles in a standardized procedure; the rest of the vegetables were untreated, and then oven dried at 80 o C for 24 h. At each site, the soils were sampled from the top 10 cm by means of a stainless steel trowel to avoid contamination. To ensure consistent distribution of metals in the soil samples, all materials were grounded in a microhammer cutter, and filtered via a 1.5-mm sieve (Demirezen and Aksoy, 2006;Osma et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…These samples were dehydrated in open air, and passed through a 2-mm sieve. After homogenization, the soil samples were stored in clear paper bags prior to the analysis (Demirezen and Aksoy, 2006;Osma et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…After each milling, to protect plant sample from microbial decomposition, mortar was cleaned with ethyl alcohol and distilled water. To ensure the uniform distribution of metals in sample, materials were milled in a micro-hammer cutter, sieved through a 1.5-mm sieve and kept in clean polyethylene bags (Markert, 1993;Osma et al, 2012). Lipid peroxidation level was measured using Heath and Packer method (1968) with slight modifications (Ananieva et al, 2002).…”
Section: Sample Collection and Analysismentioning
confidence: 99%